Systematic Review and Meta-Analysis of Sclerocarya birrea on Metabolic Disorders: Evidence from Preclinical Studies - Desirée Victoria-Montesinos; Pura Ballester; Pablo Barcina-Pérez; Ana María García-Muñoz (Metabolites)
Background/Objectives: Metabolic disorders, including diabetes, obesity, and cardiovascular diseases, are significant global health issues. Nutraceuticals, such as Sclerocarya birrea (SB), known for its high polyphenol content, are increasingly explored for managing these conditions. This study aims to evaluate the antihyperglycemic, hypolipidemic, and antihypertensive effects of SB in animal models to understand its potential as a natural intervention for metabolic diseases. Methods: A systematic review and meta-analysis were conducted according to PRISMA guidelines. Searches across databases like PubMed, Web of Science, Embase, and Scopus identified studies using SB in animal models of metabolic disorders. Inclusion criteria were studies with SB intervention, control groups, and quantitative measures of metabolic parameters. The study was registered with INPLASY (INPLASY2024100031). Results: The meta-analysis revealed that SB significantly reduces blood glucose levels in diabetic animal models. Acute administration of SB showed a pooled standardized mean difference (SMD) of −7.13 (95% CI: −11.44 to −2.83) at 1 h and −9.75 (95% CI: −15.92 to −3.59) at 2–4 h post-administration. Chronic administration indicated a non-significant reduction in glucose levels (SMD: −5.69, 95% CI: −16.38 to 5.01). Conclusions: SB appears to have the potential for reducing blood glucose levels and may offer benefits for other cardiometabolic risk factors, including lipid profiles and oxidative stress. However, variability in the results underscores the need for further research, including standardized animal studies and clinical trials, to confirm these effects and clarify the mechanisms by which SB may impact metabolic disorders.